Overexpression of angiotensin AT(1) receptor transgene in the mouse myocardium produces a lethal phenotype associated with myocyte hyperplasia and heart block - Hein, Lutz (The National Academy of Sciences of the USA, 1997)
Previous studies have suggested that angiotensin II (Ang II) modulates cardiac contractility, rhythm, metabolism, and structure. However, it is unclear whether the cardiac effects are due to direct actions of Ang II on the myocardium or if they are due to secondary effects mediated through the hemodynamic actions of Ang II. In this study, we used the α-myosin heavy chain (αMHC) promoter to generate transgenic mice overexpressing angiotensin II type 1 (AT(1a)) receptor selectively in cardiac myocytes. The specificity of transgene expression in the transgenic offspring was confirmed by radioligand binding studies and reverse transcription–PCR. The offspring displayed massive atrial enlargement with myocyte hyperplasia at birth, developed significant bradycardia with heart block, and died within the first weeks after birth. Thus, direct activation of AT(1) receptor signaling in cardiac myocytes in vivo is sufficient to induce cardiac myocyte growth and alter electrical conduction.